Flow Cytometry Analysis with a New FITC-Conjugated Monoclonal Antibody-3E12 for HLA-B*57:01 Rapid Screening in Prevention of Abacavir Hypersensitivity in HIV-1–Infected Patients. Issue 4 (July 2013) - Rodríguez-Sáinz, C.; Valor, L.; Hernández, D. C.; Gil, J.; Carbone, J.; Pascual-Bernaldez, M.; Rodríguez-Alcántara, F.; Martínez, I.; Vicario, J. L.; Mallal, S.; Fernández-Cruz, E.
Abstract : Background: Rapid screening for the detection of HLA-B*57:01 in the prevention of abacavir hypersensitivity in HIV-1–infected patients is a hallmark for clinical services.Objective: The aim of this work was to analyze the utility of flow cytometry with a new FITC-conjugated B-17 monoclonal antibody (mAb3E12) for HLA-B*57:01 screening in a Spanish cohort of 577 HIV-1+ individuals.Methods: Cryopreserved peripheral blood mononuclear cell samples from HIV-1+ individuals were analyzed by flow cytometry with the mAb 3E12 that recognizes both HLA-B*57 and HLA-B*58 alleles (members of the group specificity, HLA-B17). Patients' DNA samples had been previously typed for HLA-B*57:01 with PCR-SSO or PCR-SSP and additional DNA sequencing (EPI Study). The results obtained by flow cytometry were compared with the results obtained by the DNA-PCR techniques.Results: By flow cytometry, 46 samples (7.97%) were positive for HLA-B17, 530 (91.86%) were negative, and 1 (0.17%) was undetermined. All samples found negative by flow cytometry were negative for HLA-B*57:01 by DNA-PCR. Of the HLA-B17 positive samples, 31 (67.4%) were positive for HLA-B*57:01, 2 (3.25%) were positive for HLA-B*57:03, 11 (26.1%) were positive for HLA-B*58, and 2 (3.25%) were negative for both HLA-B*57 and HLA–B*58 antigens. The undetermined sample was negative for HLA-B*57 and HLA-B*58 alleles by DNA-PCR.Conclusions: This study shows that flow cytometry with mAb3E12 is a highly sensitive method (no false negatives) to implement prior to DNA-PCR analysis for rapid screening of HLA-B*57:01. Additional confirmation by molecular HLA typing method would be required in less than 10% of the cohort of HIV-1–infected individuals.